DUPONT SYSTEM ANALYSIS FOR MEASURING FINANCIAL PERFORMANCE OF COSMETICS COMPANIES AND HOUSEHOLD GOODS LISTED ON INDONESIA STOCK EXCHANGE PERIOD 2011-2016 - Astriani Puji Lestari; Nor Norisanti; Asep M Ramdan (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2018)
The purpose of this research is to measure the financial performance of cosmetics companies and household goods listed on the Indonesia Stock Exchange period 2011-2016 using DuPont System analysis techniques including net profit margin (NPM), asset turnover (ATO), return on assets (ROA), equity multiplier (EM), return on equity (ROE). This research uses descriptive method, secondary data used is company documentation and financial report in the form of balance sheet and income statement of PT. Akasha Wira International Tbk, PT. Kino Indonesia Tbk, PT. Mandom Indonesia Tbk, PT. Martina Berto Tbk, PT. Mustika Ratu Tbk and PT. Unilever Indonesia Tbk in 2011 until 2016. The results showed that the performance of cosmetics companies and household goods experienced fluctuations in return on equity (ROE), PT. Unilever Indonesia Tbk is a company that has good financial performance because it has net profit margin value, asset turn over, return on asset, equity multiplier and return on equity is highest compared to other similar companies in the sub sector during the period 2011-2016. Keywords: Financial performance, Net Profit Margin (NPM), Asset Turn Over (ATO), Return On Assets (ROA), Equity Multiplier (EM), Return On Assets (ROE)[bold]